Drug utilization pattern and analysis of quality of life in Indian patients of Parkinson’s disease - Shah, Jugal; Joshi, Pranav; Sood, Shikha V.; Rana, Devang; Malhotra, Supriya D. (International Journal of Basic & Clinical Pharmacology, 2019)
Background: Parkinson’s disease (PD) is a highly debilitating disease characterized by tremors, bradykinesia and rigidity. It leads to lowered self-esteem and psychological consequences which affect quality of life. The aim of this study is to study the drug utilization pattern and assess the quality of life in patients of Parkinson’s Disease. Methods: 40 patients of PD at least 1 month duration and 20 age-based controls were analyzed for quality of life using Parkinson’s Disease Questionnaire-39 (PDQ-39). Drug prescriptions were analyzed. Results: Mean number of anti-Parkinson drugs prescribed is 2.65±1.21. Of 106 anti-Parkinson drugs prescribed, 45% were levodopa and carbidopa combinations, followed by dopamine agonists (18%), anticholinergic drugs (15%), amantadine (12%), MAO inhibitors (5%) and COMT inhibitors (5%). There were significant problems in speech, performance of daily chores and daytime somnolence (p<0.0001). Depression, isolation, cognitive decline and memory loss were noteworthy in the patients as compared to controls (p<0.05). 25% patients felt embarrassed due to their disease; 59% felt affected by others’ opinion, 60% felt difficulty in communicating with others (p<0.05). Almost 2/3rd patients needed help in personal care as compared to the control group (p<0.0001). Conclusions: Quality of life of parkinsonian patients is severely affected in spite of them receiving a large number of drugs. This may be both due to disease progression as well as medication. Levodopa-carbidopa combination is the most prescribed medication. Use of levodopa and carbidopa combination must be evaluated properly. Newer guidelines and interventions are the need of the hour which may provide a better outcome on the quality of life of parkinsonian patients.